Online communication as a window to conspiracist worldviews - Wood, Michael J.; Douglas, Karen M. (Frontiers in Psychology, 2015)
In spite of the social stigma surrounding them, conspiracy theories are a common topic of public debate on the Internet. The content and tone of these discussions provide a useful insight into the structure of conspiracist belief systems and the psychological characteristics of those who believe and disbelieve in conspiracy theories. In this focused review, we relate patterns of behaviour found in online comments to the broader research literature on the psychology of conspiracy theories. Most notably, as conspiracism has its basis in disbelieving a mainstream or received narrative rather than in believing a specific alternative, most conspiracist arguments tend to fall along those same lines. Finally, we examine the implications of this methodology for future research into online discussion, particularly among hard-to-research populations.